CD147 Promotes Melanoma Progression Through Hypoxia-Induced MMP2 Activation - Zeng, W.; Su, J.; Wu, L.; Yang, D.; Long, T.; Li, D.; Kuang, Y.; Li, J.; Qi, M.; Zhang, J.; Chen, X. (Current Molecular Medicine, 2014)
Hypoxia enhances MMP2 expression and the invasion and metastatic potential of melanoma cells. CD147 has been shown to induce MMP2 in multiple cancers. To investigate the role of CD147 in hypoxiainduced MMP2 activation, we performed immunohistochemistry (IHC) staining in 206 normal and melanoma tissue samples, and analyzed the correlation between HIF1α and CD147. ChIP (chromosome Immunoprecipitation) in melanoma cell lines supports that HIF1α directly binds to CD147 promoter. Moreover, we made a series of deletion mutants of CD147 promoter, and identified a conserved HIF1α binding site. Point mutation in this site significantly decreased CD147 response to hypoxia. Importantly, knocking down CD147 attenuates MMP2 response to hypoxia in melanoma cell lines. MMP2 could not be efficiently activated by hypoxia in CD147 depletion cells. ELISA data showed that MMP2 secretion was reduced in CD147 depletion cells than control under hypoxia condition. To verify the data from cell culture model, we performed in vivo mouse xenograft experiment. IHC staining showed reduced MMP2 level in CD147 depleted xenografts compared to the control group, with the HIF1α level being comparable. Our study demonstrates a novel pathway mediated by CD147 to promote the MMP2 activation induced by hypoxia, and helps to understand the interplay between hypoxia and melanoma progression.
Keywords: melanoma